Kind of cruel [large type] - Hannah, Sophie, 1971- (Thorndike Press, 2013)
Amber Hewerdine has been suffering from chronic insomnia ever since her best friend's tragic death. As a last resort she visits a hypnotherapist, doubtful that anything will really change. Under hypnosis, Amber hears herself saying "Kind, cruel, kind of cruel." The words awaken a vague memory, but she dismisses the whole episode as nonsense. But two hours later, Amber is arrested for the brutal murder of a woman she's never heard of. And the only way she can clear her name is by remembering exactly where she's seen those words.